The depletion of doxycycline residues in poultry tissues - Mestorino, Olga Nora (2016)
Doxycycline (DOX), tetracycline of second generation, is active against Gram+ and Gram- bacteria, aerobic and anaerobic. Although there are few pharmacokinetic studies in chickens, it is frequently used for colibacillosis treatment, salmonellosis, staphylococcal infections, avian mycoplasmosis and chlamydia. Our objective was to evaluate the withdrawal time (WT) of DOX formulation at 25% in edible tissues, after PO use in 40 healthy broilers (30-35 days of age). DOX was administered through medicated drinking water for 5 days at 10 mg kg-1 (N = 36). Four untreated animals were reserved as controls. Six animals per group were sacrificed by exsanguination, after 24 h until 9 d post treatment when control animals were sacrificed as well. Muscle, liver, kidney and skin/fat samples were obtained. DOX was determined by HPLC with UV detection. DOX concentrations were determined in all tissues examined; generally falling below the MRL at 7 d after administration is terminated. The calculated WTs were 6.58, 8.18, 8.69 and 6.96 d for muscle, liver, kidney and skin/ fat, respectively. After DOX administration at a rate of 10 mg kg-1 for 5 days through the drinking water, the WT must be 9 d before treated chickens can be consumed.